Interval Sentinel Lymph Nodes: An Unusual Localization in Patients with Cutaneous Melanoma - A. M. Manganoni; R. Farfaglia; E. Sereni; C. Farisoglio; C. Pizzocaro; D. Marocolo; F. Gavazzoni; L. Pavoni; P. Calzavara-Pinton (Hindawi Limited, 2011)
Background. Recent studies have demonstrated that there exists a great variation in the lymphatic drainage in patients with malignant melanoma. Some patients have drainage to lymph nodes outside of conventional nodal basins. The lymph nodes that exist between a primary melanoma and its regional nodal basin are defined "interval nodes". Interval node occurs in a small minority of patients with forearm melanoma. We report our experience of the Melanoma Unit of University Hospital Spedali Civili Brescia, Italy. Methods. Lymphatic mapping using cutaneous lymphoscintigraphy (LS) has become a standard preoperative diagnostic procedure to locate the sentinel lymph nodes (SLNs) in cutaneous melanoma. We used LS to identify sentinel lymph nodes biopsy (SLNB) in 480 patients. Results. From over 2100 patients affected by cutaneous melanoma, we identified 2 interval nodes in 480 patients with SLNB . The melanomas were both located in the left forearm. The interval nodes were also both located in the left arm. Conclusion. The combination of preoperative LS and intraoperative hand-held gamma detecting probe plays a remarkable role in identifying these uncommon lymph node locations. Knowledge of the unusual drainage patterns will help to ensure the accuracy and the completeness of sentinel nodes identification.